“Three ladies leading the celebration”: Creations of Femininity in Stanisław Vincenz’ "Barwinkowy wianek" - Serafin, Ewa (Literatura Ludowa. Journal of Folklore and Popular Culture, 2021)
This article is an attempt at analyze and interpret the creation of female characters of Stanisław Vincenz’ novel Barwinkowy wianek. It can be concluded that Vincenz used the traditional repertoire of creating female characters, drawing on romanticism and modernism. This repertoire contains mythical, archetypal and biblical images, as well as patriarchal social patterns and phantasms, all of which were identified in the text. The social roles of grandmothers, mothers, wives, maids, nannies, servants were set in the realities specific to each described culture. The descriptions of the female body tend to be “disembodied” in the novel. The images of women in Barwinkowy wianek oscillate between spirituality (“an angel”, “a queen”, “a princess”, “woman-soul”, God Mother, a mother feeder), infantilisation (“a woman-child”) and descriptions of social oppression (corset fashion, conventions, violence). However, in most cases the women are shown in festive, ideal situations. The article looks at the meanings of the characters through the symbolism of numbers and symbolism of archetypal femininity (great Mother Goddess Sophia, light and dark faces of Shekhina).